METHODS OF STUDY OF TECHNOLOGY ELECTRONIC DOCUMENT IN THE FORM OF BUSINESS GAMES - Nataliy I. Pavlova; Gennady M. Scheglov (Открытое образование (Москва), 2016)
Joint activity of students in the development of teaching material promotes the exchange of skills and knowledge, the development of collective solutions, that is, the ability to work in a team of employees. Business Game simulating the behavior of professionals in the functioning of the SED, promotes vigorous activity students deep penetration into study disciplines, increasing the level of development of the subject.